Investigating metacognitive knowledge in reading comprehension: The case of Indonesian undergraduate students - Hamiddin, H.; Saukah, Ali (Universitas Pendidikan Indonesia, 2020)
Myriad studies have conveyed that metacognition is a key to successful reading comprehension in language classes. However, these studies focus on metacognitive strategies, metacognitive awareness, and metacognitive skills in ESL reading contexts. Anchored by the lack of empirical works on the EFL reading situation, this study investigated the metacognitive knowledge of Indonesian undergraduate students in their reading classes. Data were obtained through in-depth interviews with four successful and four less successful EFL students. The results of this study portrayed that successful readers encompass more metacognitive knowledge, awareness, motivation, and behavior if compared to the less successful readers. It is also evidence that students with good cognition, habit, and attitude in reading activities are more successful in their EFL reading, and their cognition, habit, and attitude serve as essential elements in constructing their metacognitive knowledge. Suggestions are also discussed at the end of this paper.